PERAN ORANG TUA : KOMUNIKASI TATAP MUKA DALAM MENGAWAL DAMPAK GADGET PADA MASA GOLDEN AGE - Rahma Hidayati (Universitas Teuku Umar, 2019)
It is undeniable that the presence of technology such as gadgets has changed the communication between parents and their children. Gadgets are a result of technological developments created in the form of small devices. Based on this, the researchers wanted to see how the role of parents in communicating face to face in the golden age of the existence of gadgets that are present in the midst of their lives. The approach in this study is a qualitative approach with studies that result from descriptive data in the form of speech or writing and the behavior of the people observed in addition to using reading references as the main source. From the results of the study found that there are negative and positive impacts in the use of gadgets during the golden age. The role of parents is needed to assist their children in using gadgets Keyword : parental role, face to face communication, gadget impact, golden age